Estágio curricular supervisionado na compreensão de estudantes do ensino médio integrado à educação profissional: um estudo na Amazônia Oriental - NASCIMENTO FILHO, Antônio Rodrigues do (2024)
This research was developed within the scope of the Professional Master's Program in Professional and Technological Education (ProfEPT), at the Federal Institute of Education, Science and Technology of Amapá (IFAP), Campus Santana. The topic covered was supervised curricular internship in secondary technical professional education, articulated in an integrated way. The study of the topic in question was developed based on the perception of students at the Instituto Federal do Amapá, Campus Laranjal do Jari. It aimed to analyze the understanding of students in the third year of integrated high school (graduates) about the mandatory supervised curricular internship. The research sought to answer the following problem: students in the third year of integrated high school at IFAP, on the Laranjal do Jari campus, understand the mandatory supervised curricular internship as a pedagogical practice that results in a contribution to their professional, intellectual, social and social training. prepare them to enter the world of work? As data collection instruments, the investigation made use of bibliographical and documentary research and the application of a questionnaire to students. The approach adopted was qualitative and also quantitative. In general, the results indicated that the majority of students surveyed understand the concept of internship and recognize its importance for professional training. However, the study also revealed the existence of gaps regarding clarifications about guidelines, regulations, evaluations and monitoring by supervisors and internship advisors. To address these gaps, an educational product was created: a booklet containing general guidelines on supervised curricular internship. It is expected that this booklet, together with other pedagogical strategies, will contribute to strengthening the understanding of the internship and serve as a guide for course coordinators, internship management sectors on campus and for students. Offering them a more comprehensive understanding of the supervised curricular internship in every context in which it is inserted at EPTNM.